Carp edema virus in Polish aquaculture – evidence of significant sequence divergence and a new lineage in common carp Cyprinus carpio (L.). Issue 3 (25th July 2016) - Matras, M; Borzym, E; Stone, D; Way, K; Stachnik, M; Maj‐Paluch, J; Palusińska, M; Reichert, M
Abstract: Fish samples initially collected by local veterinarians on the common and koi carp farms in Poland between 2013 and 2015 as part of a KHV surveillance programme, when the water temperature was between 16 and 26 °C, and were also tested for CEV by qPCR. A partial 478 nucleotide fragment of the 4a gene was subsequently generated from 17 qPCR‐positive common carp Cyprinus carpio samples from 36 farm sites tested during the period. Sequence alignments and analysis revealed the presence of CEV in Poland both in common carp as well as in koi carp farms, and phylogenetic analysis assigned the Polish CEV sequences into three distinct genogroups. A lineage which includes the original sequences obtained from koi carp in Japan (genogroup II) included sequences from both koi carp and common carp, and the second lineage (genogroup I) contained sequences from common carp only. A third lineage (genogroup III) which was more closely related to the genogroup II also consisted of sequences from common carp only. The latter represents a lineage of CEV not previously described in the literature.